Policy Implementation Program to Alleviate Uninhabitable Houses for the Poor - Rizal Panji Nagayoso; Kridawati Sadhana; Yuntawati Fristin (LPPM Institut Teknologi dan Sains Mandala, 2025)
This research aims to describe and analyze the alleviation program of uninhabitable houses (RTLH) and identify supporting factors, obstacles, and implementation efforts. The research was conducted in Kepanjen Sub-district, Malang Regency. The data analysis technique used qualitative analysis. The findings show that the RTLH assistance program in Kepanjen Sub-district significantly benefits people experiencing poverty, such as improved building quality, health, and welfare. The program was implemented with the active role of the village and neighborhood group governments in collecting data on residents in need and supported by good socialization that facilitated the implementation process. The main supporting factors include cooperation between related parties, clear regulations, and active participation of residents. However, there are obstacles in the complicated procedures for distributing assistance, limited funds that cause some residents not to be covered, long bureaucracy, and land issues that do not belong to residents. Efforts are needed to overcome these obstacles. It is hoped that related parties will simplify overlapping regulations and increase funding allocations so that the RTLH program can cover more poor people to alleviate poverty.